THE VIBRANT FORM OF BIHAR’S FOLK ART: PAPIER-MÂCHÉ - Ranjan, Rajeev; Kumar, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Bihar’s folk art includes Mithila (Madhubani) painting, Manjusha art, Tikuli art, Sikki art, Sujni embroidery, and terracotta craft, along with Papier-mâché, which is also a significant folk art form. This craft involves blending paper pulp, Multani mitti (Fuller’s earth), fenugreek powder, and other materials to create various toys, sculptures, and decorative objects. It remains a traditional and eco-friendly art form, preserving the natural essence of recycled or used paper pulp. Papier-mâché is used not only by folk artists but also by contemporary artists as a medium of artistic expression. This research paper highlights the unique techniques, designs, and social and cultural contexts of Bihar’s Papier-mâché art. Additionally, it addresses the role of the Bihar government in preserving the cultural identity of this art form and providing economic support to local artists. For this study, interviews were conducted with senior artists who provide training at the Upendra Maharathi Shilp Anusandhan Kendra, Patna—an institution dedicated to the preservation and training of Bihar’s folk arts—as well as young artists who have received training there. This research paper also includes a comparative analysis of the creative processes of Papier-mâché art from Bihar, Odisha, and Kashmir.